Greening and ‘De-concreting’ of Polish Cities – Directions, Best Practices and Recommendations - Rynio, Dorota; Sokołowski, Jakub; Zakrzewska-Półtorak, Alicja (Zazielenianie i „odbetonowanie” polskich miast – kierunki, dobre praktyki, rekomendacje, 2023)
The purpose of the paper was to identify and assess the directions of changes in the development of urban space in Poland in terms of greening and ‘de-concreting’ (‘decementification’), as well as to formulate preliminary recommendations in this regard. The research selected the following Polish cities: Warsaw, Kraków, Wrocław, Gdańsk, Katowice, and Lublin. The primary methods used in the study were literature and source materials analysis, comparative analysis, and case study. As a result, three different groups of actions taken in Polish cities to fight ‘concretosis’ (cementification) were identified. It was also found that there is still a lot of scope for expanding these actions, both in terms of tools and areas of urban space affected by changes. Finally, the authors proposed recommendations that may facilitate Polish city planning, ‘de-concreting’, and greening.
Biblioteka Regionalisty = Regional Journal, 2023, Nr 23, s. 96-102
Keywords: urban space; concretosis; cementification; quality of life; climate change; municipal greenery; przestrzeń miejska; betonoza; jakość życia; zmiany klimatyczne; zieleń miejska